Performance analysis of different sac-ocdma codes for indoor visible light communication system - Idriss, Yahaya (2016)
Indoor visible light communications (VLC) are promising technology where light-emitting-diode (LEDs) are used to transmit data in the form of visible light (white-light) in free space. This technology gains several attractions due to its free licenses, and abundant unregulated bandwidth in the optical spectrum region. It is evident that indoor VLC systems are susceptible to ambient light noise that causes interference which tends to degrade communication channel. Recently, Hadamard matrix code was applied to the indoor VLC system in order to achieve a low error probability in LED-based system. However, with the results obtained, there is a need for improvement by analyzing other SAC-OCDMA code. Therefore, this research focuses on the performance analysis of different spectral amplitude coding optical code division multiple access (SAC-OCDMA) codes for an indoor visible light communication system. This is to provide a better quality of service (QoS) with a lower bit error rate (BER), high signal to noise ratio (SNR) for a long transmission distance for indoor use, under the influence of both direct sunlight with a filter and indirect sunlight without a filter. In order to achieve this, a proper choice of the system components such as a transmitter, modulation format, coding, filtering, and the receiver were made. This can be evaluated through computer simulations, by analyzing the bit error rate (BER), signal to noise ratio (SNR), received the optical power signal and the eye diagram performance. The results obtained from the simulation shows that among the three codes that were subjected to the influence of background light noise interference. KS code offers a significant improvement of 21.05% difference in term of propagation distance, by achieving a long transmission distance under the influence of indirect sunlight without a filter and direct sunlight with a filter at a bit rate of 622 Mbps, with also 11.76 % improvement in transmission distance with 1Gbps bit rate. It is evident from the result that KS code can perform better under the influence of indirect sunlight without a filter, which is the major source of ambient light noise interference in an indoor environment. Therefore, this research proposed a model that can be used as a solution for the next generation of indoor VLC system, employing SAC-OCDMA optical access network.